Gambaran sidik bibir mahasiswa pada Fakultas Kedokteran Gigi Universitas Hasanuddin (Lip print imaging of students at Faculty of Dentistry Hasanuddin University) - Syamsiar Toppo; Irene Edith Rieuwpassa; J. I. Lisal; Ummi Salmiah Sari (Journal of Dentomaxillofacial Science, 2014)
Cheiloscopy is the study of lip print used to identify a person. Like finger print, lip print patterns recently are proven tohave differences in each individual. Groove on the lip is fixed and cannot be changed. Following Suzuki method, lipprint pattern is divided into 6 types, namely complete vertical groove, incomplete vertical groove, branched groove,groove intersected, groove reticular, and undifferianted. The purpose of this study was to determine the lip printpattern of Indonesian people, especially the students of the Faculty of Dentistry, University of Hasanuddin. Thisresearch was conducted at the Faculty of Dentistry, Hasanuddin University. Using random sampling technique, thesample of the study consisted of 50 subjects that include men and women in the age group 20-24 years. The lips thathave been smeared with lipstick are open on its normal position, smile and the kiss is record. Masking tape is attachedat various positions on the lips and then the tape is attached to the paper to be observed. Data are analysed with amagnifying glass and classified according to the "Classification Tsuchihashi and Suzukis. The study found all lip printsshow different patterns. The pattern of lip prints is not only made up of only one type of groove, but appears as amixture of various types. The pattern of lip prints is generally found in type II and type V is the least found. The studyconcludes that no difference in the pattern of individual lip prints on a wide range of positions in the normal, open,smile and kiss positions.